Relationships between childhood trauma and dissociative, psychotic symptoms in patients with schizophrenia: a case–control study. Issue 1 (27th January 2022) - Uyan, Tugce Taskin; Baltacioglu, Mehmet; Hocaoglu, Cicek
Abstract : Background: Childhood trauma (CT) is an important risk factor in the emergence and clinical course of psychiatric disorders. In the latest literature, an association exists between CT and patients with schizophrenia. There is also a strong relationship between the dissociative symptoms of schizophrenia and the presence of CT. Aims: The aim of this study is to examine the relationship between CT and dissociative, positive and negative symptoms in patients with schizophrenia. Methods: One hundred patients with schizophrenia and 100 healthy volunteers were included in the study. The Sociodemographic Data Form, Dissociative Experiences Scale (DES), Positive and Negative Syndrome Scale (PANSS), and Childhood Trauma Questionnaire (CTQ) were administered to all participants. Results: The CTQ and DES scores of the schizophrenia group were significantly higher than those of the control group. In patients with schizophrenia, a positive association was found between positive symptoms and DES scores. In terms of negative symptoms, a positive association was found between apathetic social withdrawal and CTQ-emotional neglect (EN), CTQ-physical neglect (PN) and CTQ total scores. There was a significant positive correlation between CTQ-EN scores and negative symptoms and PANSS scores. No significant relationship was found between negative symptoms and DES scores. Conclusions: High rates of CT and dissociative symptoms are seen in patients with schizophrenia. In addition, the findings of the relationship between CT and dissociative, positive and negative symptoms are also noteworthy. Therefore, it may be important for clinicians to assess trauma history during the psychiatric evaluation of patients with schizophrenia.